Challenges of Science Teachers in Designing Inquiry Learning: A Systematic Literature Review - Setiyani, Amira; Munfaridah, Nuril; Hidayat, Arif (Kasuari: Physics Education Journal (KPEJ), 2025)
This study aims to map the challenges faced by science teachers in designing inquiry-based learning through a systematic literature review (SLR) approach. The PRISMA method was used to screen articles from the ERIC database published between 2020 and 2025. Out of 292 initial articles, a rigorous inclusion-exclusion process narrowed the sample to 14 relevant studies, which were then thematically analyzed. The findings revealed nine major thematic challenges: limited understanding of inquiry, lack of experience, reliance on traditional teaching methods, difficulty integrating inquiry into classroom practice, insufficient institutional support, inadequate professional development, challenges in designing inquiry elements, time constraints, and unsupported assessment practices. These challenges are interrelated and reflect the multidimensional nature of barriers to effective inquiry-based science instruction. This study provides empirical contributions to support science education policy development and the design of teacher training programs responsive to 21st-century learning demands.